Vitamin D and Calcium Supplement Attenuate Bone Loss among HIV-Infected Patients Receiving Tenofovir Disoproxil Fumarate/Emtricitabine/Efavirenz: An Open-Label, Randomized Controlled Trial - Boontanondha, Patawee; Nimitphong, Hataikarn; Musikarat, Suchawadee; Ragkho, Aschara; Kiertiburanakul, Sasisopin (Current HIV Research, 2020)
Background: Antiretroviral therapy (ART), especially with tenofovir disoproxil fumarate (TDF), has been associated with accelerated bone turnover and leads to significant bone loss. Objective: We aimed to determine the effect of vitamin D2 and calcium on bone mineral density (BMD) in HIV-infected patients receiving TDF/emtricitabine (FTC)/efavirenz (EFV). Methods: A prospective, open-label, randomized controlled study was conducted. Eligible patients were ART naïve HIV individuals who initiated TDF/FTC/EFV. The study group received supplementation with vitamin D2 and calcium carbonate, whereas the control group was administered only ART. The primary outcome was the percentage change in total hip BMD at week 24 compared with baseline. Results: A total of 18 patients were randomized (9 in each group). The mean (standard deviation; SD) total hip BMD significantly decreased from baseline in both groups, from 0.96 (0.14) g/cm2 to 0.93 (0.13) g/cm2 in the study group (p = 0.006) and from 0.87 (0.11) g/cm2 to 0.84 (0.11) g/cm2 in the control group (p = 0.004). The mean (SD) lumbar spine BMD significantly decreased from baseline in both groups, from 1.00 (0.13) g/cm2 to 0.97 (0.13) g/cm2 (p = 0.004) in the study group and from 0.90 (0.09) g/cm3 to 0.86 (0.08) g/cm2 in the control group (p = 0.006). At week 24, the mean (SD) lumbar spine BMD was significantly greater in the study group than in the control group (p = 0.042). However, there were no significant differences in the percentage change of total hip, lumbar spine, and femoral neck BMD between both groups. No adverse events were reported. In conclusion, as early as 24 weeks after TDF initiation, a significant decline in BMD was detected. Conclusion: Vitamin D2 and calcium supplements should be considered for HIV-infected patients receiving TDF/FTC/EFV in a resource-limited setting where there are limited ART options (Clinicaltrials. gov NCT0287643).
Keywords: HIV